PENGARUH GAYA KEPEMIMPINAN, DISIPLIN KERJA DAN LINGKUNGAN KERJA TERHADAP PRODUKTIVITAS KERJA KARYAWAN CV SENA MUKTI - Irgian, Irfan; Lisdiana, Nuning; Rahayu, Listyowati Puji (Universitas Boyolali, 2023)
This study aims to determine whether the performance of CV Sena Mukti Boyolalin employees can be affected by leadership style, work discipline and work environment. A descriptive quantitative study was used as a research method. All employees of CV Sena Mukti Boyolali are the population in this study, and the sample is 42 respondents using a simple random sampling method. Hypothesis testing uses several linear regression tests. The results of this study show that leadership style has no partial effect on employee productivity, work discipline has a partial effect on employee productivity, and the work environment has a partial effect on employee productivity. Simultaneous test results show that leadership style, work discipline, and work environment simultaneously affect employee productivity.